ANALISIS POTENSI LANSKAP CANDI PENINGGALAN KERAJAAN SINGOSARI DI KABUPATEN MALANG SEBAGAI OBJEK WISATA SEJARAH - Debora Budiyono; Hendra Kurniawan; Astri Sumiati; Muh. Candra Kusumah (BUANA SAINS, 2023)
Malang Regency is an area that has many historical relics. One of the relics whose existence is preserved and can be visited is the temple landscape of the heritage of the Singosari kingdom which has the character and identity of the characteristics of the heritage of the Singosari kingdom. The Singosari Kingdom has several temples including Singosari Temple, Kidal Temple, Jago Temple, and Sumberawan Temple which are Hindu Buddhist temples based on the function, shape, and reliefs that exist in these temples. The purpose of this study is to analyze the potential of the temple landscape from the Singosari kingdom in the hope that it can be developed as a historical tourist attraction in Malang Regency, there are actions to preserve the temple landscape, and improve the economy of the local community around the temple. The research method used is descriptive quantitative. Based on the results of the analysis of existing path aspects, historical aspects, objects and attractions aspects, and visual aspects of the landscape in the landscape of the Singosari Temple, Kidal Temple, Jago Temple, and Sumberawan Temple, it shows that the four temples have the potential to be developed as historical tourism relics of the Singosari Kingdom in Malang Regency.